Maximizing the Development Impacts from Temporary Migration : Recommendations for Australia’s Seasonal Worker Program - World Bank (World Bank, Washington, DC, 2018)
The seasonal worker program (SWP) was formally introduced in 2012 following a four-year pilot scheme. The program maintains the dual objectives of: (i) contributing to the economic development of nine participating Pacific Island countries and Timor-Leste; and (ii) filling labor shortages in the Australian agriculture sector, accommodation sector (in selected locations), and tourism sector (the Northern Australia tourism pilot). This paper assesses the first of these objectives, evaluating the impact of the SWP on workers, their households, and communities. In doing so, it aims to build on the evidence already collected on the development impacts of the Pacific seasonal worker pilot scheme and shed further light on how the program can be improved to increase the benefits flowing through to the Pacific region.